2022
DOI: 10.2478/ama-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Fuzzy Fractional Order Adaptive Impedance Controller with Integer Order Approximation for Stable Robotic Contact Force Tracking in Uncertain Environment

Abstract: Current research in robot compliance control is unable to take both transient contact force overshoots and steady-state force tracking problems into account. To address this problem, we propose a fuzzy fractional order (FO) adaptive impedance controller to avoid the force overshoots in the contact stage while keeping force error in the dynamic tracking stage, where traditional control algorithms are not competent. A percentage gain is adopted to map FO parameters to integer order (IO) parameters by their natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In practice, however, the dynamic and complex uncertainty of the external physical environment and the difficulty of predicting environmental parameters in advance make impedance control systems often perform poor force tracking characteristics, stability and robustness. To solve this problem, a series of admittance control algorithms are proposed, such as environment identification (Xu, 2016; Seraji and Colbaugh, 1997), adaptive control (Cao et al , 2019; Duan et al , 2018; Jung et al , 2004), neural networks (Hamedani et al , 2021; Peng et al , 2019; Jung and Hsia, 2010; Liang et al , 2019), and fuzzy logic (Liu et al , 2022; Cao, 2022; Li et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, however, the dynamic and complex uncertainty of the external physical environment and the difficulty of predicting environmental parameters in advance make impedance control systems often perform poor force tracking characteristics, stability and robustness. To solve this problem, a series of admittance control algorithms are proposed, such as environment identification (Xu, 2016; Seraji and Colbaugh, 1997), adaptive control (Cao et al , 2019; Duan et al , 2018; Jung et al , 2004), neural networks (Hamedani et al , 2021; Peng et al , 2019; Jung and Hsia, 2010; Liang et al , 2019), and fuzzy logic (Liu et al , 2022; Cao, 2022; Li et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2020) investigated the effect of the inertia and damping terms in the conventional impedance equation when they are of fractional order on the stability and robustness of the system, proposed a fractional-order impedance control strategy with faster response, lower overshoot and good tracking performance and verified the stability of this control algorithm theoretically. In Cao (2022), the authors proposed a fuzzy fractional-order admittance controller based on percentages, which has greater stability and robustness with respect to the classical integer-order impedance controller. However, the above fractional-order admittance algorithms have difficulty in showing good force tracking performance in highly dynamic changing environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A fuzzy fractional order (FO) adaptive impedance controller was presented on the robot manipulator to prevent force overshoots in the contact stage while keeping force error in the dynamic tracking stage where conventional control methods are ineffective [10]. The simulation results showed that the suggested controller can be designed to be more stable and superior to the general impedance controller and the force tracking results have also been compared to earlier control methods.…”
Section: Introductionmentioning
confidence: 99%